Adenoid Cystic Carcinoma (ACC) of the Bartholin's gland misdiagnosed for three times: a case report - Moustafa Alhashemi; Sana Oubari; Aya Haji Mohamad; Mohamad Alhashemi; Obaida Kabel; Afaf Alhelue; Farah Fattal (BMC, 2023)
Abstract Background Adenoid cystic carcinoma (ACC) in Bartholin's gland is an uncommon malignant tumor. These tumors have a vague clinical feature, so they are diagnosed late and discovered at a high-level stage. Our case presented Three Recurrences and Three times Misdiagnosis of Adenoid Cystic Carcinoma (ACC). Case presentation We report a case of adenoid cystic carcinoma arising in Bartholin's gland of a 64-year-old female patient that appeared after three previous vulvar tumors were excised. The patient underwent bilateral radiotherapy which was performed on the perineum. Conclusion ACC of the vulvar sweat glands is prone to misdiagnosis and delay in both diagnosis and treatment. As seen in our case, it was misdiagnosed three times as Chondroid Syringoma. Further studies need to be conducted to better understand the tumor prognosis, and its optimal treatment options.